Genetics and developmental biology of cooperation. Issue 17 (21st July 2017) - Kasper, Claudia; Vierbuchen, Maddalena; Ernst, Ulrich; Fischer, Stefan; Radersma, Reinder; Raulo, Aura; Cunha‐Saraiva, Filipa; Wu, Min; Mobley, Kenyon B.; Taborsky, Barbara
Abstract: Despite essential progress towards understanding the evolution of cooperative behaviour, we still lack detailed knowledge about its underlying molecular mechanisms, genetic basis, evolutionary dynamics and ontogeny. An international workshop "Genetics and Development of Cooperation, " organized by the University of Bern (Switzerland), aimed at discussing the current progress in this research field and suggesting avenues for future research. This review uses the major themes of the meeting as a springboard to synthesize the concepts of genetic and nongenetic inheritance of cooperation, and to review a quantitative genetic framework that allows for the inclusion of indirect genetic effects. Furthermore, we argue that including nongenetic inheritance, such as transgenerational epigenetic effects, parental effects, ecological and cultural inheritance, provides a more nuanced view of the evolution of cooperation. We summarize those genes and molecular pathways in a range of species that seem promising candidates for mechanisms underlying cooperative behaviours. Concerning the neurobiological substrate of cooperation, we suggest three cognitive skills necessary for the ability to cooperate: (i) event memory, (ii) synchrony with others and (iii) responsiveness to others. Taking a closer look at the developmental trajectories that lead to the expression of cooperative behaviours, we discuss the dichotomy between early morphological specialization in social insects and more flexible behavioural specialization in cooperatively breeding vertebrates. Finally, we provide recommendations for which biological systems and species may be particularly suitable, which specific traits and parameters should be measured, what type of approaches should be followed, and which methods should be employed in studies of cooperation to better understand how cooperation evolves and manifests in nature.